Pendidik Dalam Pendidikan Islam - Idham, Muhammad; G, Gusmaneli (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Education in the Islamic perspective is not merely about transferring knowledge, but also about shaping character and spirituality. In Islam, education holds a central role as a means of drawing closer to God and forming individuals with noble morals. Core values such as honesty, responsibility, and compassion are emphasized throughout the learning process. The Prophet Muhammad (peace be upon him) is regarded as the ultimate educator, whose life serves as a model in all aspects. In today’s modern world, Islamic education faces new challenges, especially in aligning religious values with advancements in science and technology. Therefore, the approach must go beyond the cognitive—reaching into the emotional and spiritual dimensions of the learner. Ideally, Islamic education should be able to produce individuals who are intelligent, faithful, and capable of contributing positively to society and global civilization